Predictors of Failure in Ultrasound-Guided Hydrostatic Reduction of Intussusception in Children: Retrospective Analysis in a Specialized Center in Ethiopia - Wondemagegnehu BD; Kerego EN; Mammo TN; Robele AT; Gebru FT; Aklilu WK (Dove Medical Press, 2024)
Belachew Dejene Wondemagegnehu,1 Ephrem Nidaw Kerego,2 Tihtina Negussie Mammo,1 Amezene Tadesse Robele,1 Fisseha Temesgen Gebru,1 Woubedel Kiflu Aklilu1 1Department of Surgery, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Surgery, St. Paul's Millennium Medical College, Addis Ababa, EthiopiaCorrespondence: Belachew Dejene Wondemagegnehu, Lideta Sub City Churchill Road, Zambia St, Addis Ababa, 26038, Ethiopia, Email belachew99@yahoo.comPurpose: To identify factors predicting the failure of ultrasound-guided hydrostatic reduction of intussusception in children.Patients and Methods: The medical records of 174 children who underwent ultrasound-guided hydrostatic reduction of intussusception over four years were reviewed at Tikur Anbessa Specialized Hospital. Patient's demography, clinical data, and sonography findings (type of intussusception, length of intussusception, presence of lead point, trapped fluid, lymph node, and free peritoneal fluid) were entered into SPSS 25 (IBM) and analyzed using logistic regression.Results: The overall success rate of ultrasound-guided hydrostatic reduction was 81.6%. The sex, presence of abdominal cramps, vomiting, diarrhea, trapped lymph nodes on ultrasound, or history of upper respiratory tract infection had no association with hydrostatic reducibility. Currant jelly stool (OR 0.128; 95% CI, 0.27- 0.616; P=0.01), Ileo-ileo colic intussusception (OR 0.055; 95% CI, 0.005- 0.597; P=0.017), pathologic lead point (OR 0.66; 95% CI, 0.01- 0.447; P=0.005) and abdominal distention (OR 0.209; 95% CI, 0.044- 0.998; P=0.048) showed significant association with failed hydrostatic reduction.Conclusion: The presence of currant jelly stool, ileo-ileo colic type intussusception, pathologic lead point, and abdominal distention are the most important predictors for failed ultrasound ultrasound-guided reduction intussusception in children.Plain Language Summary: Intussusception occurs when an upper part of the bowel invaginate into the lower adjacent segment. Usually, the small intestine slides into the wider large intestine. It is the common cause of gut obstruction in children below 3 years of age. It occurs in 2 out of 1000 children, and the cause is not known in 95% of the cases.Most of the children are treated without surgery. If left untreated may complicate life-threatening conditions. The non-surgical management is feasible in a child who is not critical. It is achieved by putting air or suitable fluids under pressure through a tube to the rectum. The fluid in the rectum flows to the intestine creating a pressure that pushes back the invaginated intestine to its normal position. The reduction is followed by an ultrasound of the belly. Currently, this technique is widely practiced with reasonable success rates.In some children, the reduction with this technique may fail due to different conditions. So, our study was aimed at identifying the possible factors that are responsible for the failure of reduction. The success rate of reduction during our study period was 81.6% (144/176). This study has identified that in children with blood-mixed mucous in stool during illness, the Presence of belly distention, and the presence of known causes of intussusception detected by ultrasound during the examination of the child significantly contributed to failure of non-surgical reduction.Keywords: pediatric intestinal obstruction, idiopathic intussusception, pediatric ultrasound, saline enema